“Aplicación móvil para pedidos de comida a domicilio en la ciudad de Latacunga.” - Alanuca Añarumba, Carlos Alexander (2021)
This research proposes developing a mobile application that allows ordering food from restaurants in Latacunga by using different technological tools of free software. The application has a web platform that allows the business's administration by the owners of the affiliated restaurants and, on the other hand, through a mobile platform from the customers' side. This application is a viable solution to maintain businesses' economic development and avoid the agglomeration of people in closed places to establish citizens' welfare because of the pandemic. The development of the proposal involved using an adaptation of agile practices of Scrum, which works with the incremental, iterative model that develops the software product in stages; at the end of each Sprint, available deliveries are obtained. During the software product development, relational databases such as (MySQL) and non-relational databases (Firebase) were used. We also took advantage of free software tools such as PHP, Bootstrap, Android Studio, Bootstrap, Visual Paradigm, Visual Studio Code.